2016
DOI: 10.4236/ajcc.2016.52020
|View full text |Cite
|
Sign up to set email alerts
|

Trends and Geostatistical Interpolation of Spatio-Temporal Variability of Precipitation in Northern Cameroon

Abstract: This paper examines the spatial and temporal variability of the mean annual precipitation in the Northern Cameroon on the context of climate change during the time period 1950-2013. The study used homogeneous monthly and annual precipitations database of twenty-five stations located in the Northern Cameroon and Southern Chad Republic. Geostatisticals interpolation methods (Kriging and Inverse Distance Weighting method) associated with Digital Elevation Model were used to establish the spatial distribution of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Note that, while all analyses on the spatial distributions of these indices are made for all seasons, that is, December–January–February (DJF), March–April–May (MAM), June–July–August (JJA) and September–October–November (SON), their inter‐annual variability is analysed over three zones (Zone 1: 9–12°N and 13–15°E; Zone 2: 4–6°N and 9–11°E; and Zone 3: 2–4°N and 12–16°E), selected on the basis of their high vulnerability and for their recurrent exposure to extreme events in recent years (Zogning et al, 2008; Dassou et al, 2016; Chouto and Wakponou, 2017; Tanessong et al, 2017; Saha and Tchindjan, 2017; Djuidje et al, 2019).…”
Section: Study Area Data Used and Methodologymentioning
confidence: 99%
“…Note that, while all analyses on the spatial distributions of these indices are made for all seasons, that is, December–January–February (DJF), March–April–May (MAM), June–July–August (JJA) and September–October–November (SON), their inter‐annual variability is analysed over three zones (Zone 1: 9–12°N and 13–15°E; Zone 2: 4–6°N and 9–11°E; and Zone 3: 2–4°N and 12–16°E), selected on the basis of their high vulnerability and for their recurrent exposure to extreme events in recent years (Zogning et al, 2008; Dassou et al, 2016; Chouto and Wakponou, 2017; Tanessong et al, 2017; Saha and Tchindjan, 2017; Djuidje et al, 2019).…”
Section: Study Area Data Used and Methodologymentioning
confidence: 99%
“…Kriging is a stochastic interpolation technique (Journel and Huijbregts 1978;Isaaks and Srivastava 1989) and is largely recognized as a standard approach for surface interpolation based on scalar measurements at different locations (Shahid and Behrawan 2008). Djoufack et al (2012) and Dassou et al (2016) showed that Kriging gives better global predictions than the Inverse Distance Weighting (IDW) in the current study domain.…”
Section: Kriging Interpolationmentioning
confidence: 96%
“…Climatically, this study area falls within the Sudano-Sahelian domain that portrays a high inter-annual variability in its whole area, increasing from south to north. This may be attributed to the topography of the region (Dassou et al 2016), which features lowlands with altitudes within 95 and 795 m.…”
Section: Study Area and Datamentioning
confidence: 99%
See 2 more Smart Citations